Proceso de ASC - EVALUACION DE IMPACTO DEL USO DE JUEGOS EN LA ENSEÑANZA DEL EMPRENDIMIENTO (2020)
This research aims to measure the impact of using games in teaching entrepreneurship to undergraduate students at Universidad EAFIT. For this purpose, a quantitative measurement instrument was designed based on existing tools, and virtual validation sessions were conducted with students from various programs at Universidad EAFIT.